2017
DOI: 10.1007/s00253-017-8553-5
|View full text |Cite
|
Sign up to set email alerts
|

Starvation- and xenobiotic-related transcriptomic responses of the sulfanilic acid-degrading bacterium, Novosphingobium resinovorum SA1

Abstract: Novosphingobium resinovorum SA1 was the first single isolate capable of degrading sulfanilic acid, a widely used representative of sulfonated aromatic compounds. The genome of the strain was recently sequenced, and here, we present whole-cell transcriptome analyses of cells exposed to sulfanilic acid as compared to cells grown on glucose. The comparison of the transcript profiles suggested that the primary impact of sulfanilic acid on the cell transcriptome was a starvation-like effect. The genes of the periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
9
0
2
Order By: Relevance
“…Transcriptome and proteome analysis was done for certain sphingomonads grown under certain unique physiological conditions. These omics studies showed substrate specific expression patterns of TBDTs [14,16,33,34,36,[38][39][40]. About 32 TBDTs showed differential expression in the presence of heavy metals, xenobiotics, temperature stress, and poor nutrient conditions ( Table 1).…”
Section: Tbdts Of S Fuliginismentioning
confidence: 96%
See 1 more Smart Citation
“…Transcriptome and proteome analysis was done for certain sphingomonads grown under certain unique physiological conditions. These omics studies showed substrate specific expression patterns of TBDTs [14,16,33,34,36,[38][39][40]. About 32 TBDTs showed differential expression in the presence of heavy metals, xenobiotics, temperature stress, and poor nutrient conditions ( Table 1).…”
Section: Tbdts Of S Fuliginismentioning
confidence: 96%
“…One of them showed a seven-fold increased expression when the cells were grown in sulfanilic acid. Such an increase in TBDT amounts is believed to facilitate active transport of polar sulfanilic acid across the outer membrane [36]. TonB-dependent transport system appears to be advantageous to bacteria in more than one way.…”
Section: Unique Tonb Complex In Sphingobium Fuliginismentioning
confidence: 99%
“…To date, a great variety of physico-chemical treatments have been available for removing these contaminants from the environment (Scullion 2006), but biological approaches are still among the most promising methods. Bioremediation based on natural processes utilizes the metabolic pathways of microorganisms (Laczi et al 2015;Hegedüs et al 2017;Heged} us et al 2017) (or plants) to neutralize pollutants and, thus, can be performed either ex situ or in situ (Vidali 2001;Perei et al 2001;Kang 2014;Kis et al 2015Kis et al , 2017. A decrease in contamination can be achieved by stimulating the indigenous microflora of the polluted site with nutrient addition (i.e.…”
Section: The Role Of Microorganisms In Bioremediationmentioning
confidence: 99%
“…By now, many reports have revealed different physiological states in bacteria ( Fig. 1) ranging from unstressed living cells to dead cells (Kell et al 1998;Bergkessel et al 2016;Hegedüs et al 2017); a range which includes VBNC states. VBNC cells maintain their viability but unable to grow on routinely-used laboratory media (Oliver 2005).…”
Section: Vbnc State In Bacteriamentioning
confidence: 99%
See 1 more Smart Citation